ANALISIS PERKEMBANGAN WIRAUSAHA BERBASIS ONLINE PADA USAHA MAHASISWA FKIP UNTAN. - Laras Setyaningsih; Bambang Genjik S; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This thesis is entitled "Online-Based Entrepreneurial Development Analysis on Student Business FKIP UNTAN". The method used is descriptive method. The form of the research is qualitative description. The data collection techniques in this study were: direct communication with interview guide data collection tools, direct observation with observation sheet data collection tools, documentary studies with archive data collection tools. The results of the study: 1) The development of online-based entrepreneurship in the business of FKIP UNTAN students, experiencing developments, this can be seen from all FKIP Untan student informants who run online shop businesses remain active and the types of goods sold in the online shop are also varied and so many consumers are interested in buying goods. which is offered. 2) That there are obstacles from internal factors such as financial problems, which are still small and mentally untested in facing competition and external factors faced in the development of online-based entrepreneurship, namely the problem of facilities and infrastructure, in addition to the nature of the product that is still not consistent for sold and the limited access to information obtained is because FKIP students in running a business are still not focused because they are still new and are still student status. 3) Efforts are made to continue to improve the quality of oneself by continuing to learn so as to improve business performance and increase business networks so that online shops are better known and active in conducting promotions.